Validation study of a reduced version of the Geriatric Depression Scale in Portugal - Santos, Ana João (2019)
The validity of the short Geriatric Depression Scale (GDS) version (5 items) was assessed in two samples of older adults aged 60 or more years. Concurrent validity, specificity, and sensitivity were obtained in a convenience sample of 66 individuals (mean of 70 years) by comparison to the Beck Depression Inventory (IDB-II). Factorial analysis was conducted in a population-based sample of 1023 participants (mean of 71 years). The 5-item version of the Geriatric Depression Scale presented adequate internal consistency values and good correlation results with the IDB-II. These results suggest its reliability and adequate sensitivity, and specificity values for screening for depressive symptoms in the elderly population. The results obtained by the Confirmatory Factor Analysis (CFA) suggest that the one-factor model does not have the desired characteristics – one of the items (item 4) may have a lower discriminative power and a better fit in the model obtained by the CFA for 4 items was observed.